Human rights-compliant counterterrorism : myth-making and reality in the Philippines and Indonesia / Jayson S. Lamchek. - Lamchek, Jayson S., 1974- (Cambridge University Press, 2019)
Since 9/11, we have lived in an age of counterterrorism in which the spectre of terrorism justifies increasingly repressive and violent measures. Against this backdrop, legal scholars and human rights advocates have encouraged integration of human rights into the discourse of counterterrorism as the best way to counter such repression and violence. This book challenges that received wisdom by showing the ambiguous effects of such converged discourse on developing countries. It highlights the effect of terrorism discourse on human rights in two developing countries, viz., the Philippines and Indonesia, the efforts of local advocates in resisting abuses in the name of counterterrorism, and the persistence of violations despite legal and policy reforms in those countries. Applying a novel analytic framework drawn from critical terrorism studies and critical international law, the book provokes new thinking on the future of human rights advocacy in the age of counterterrorism.